(untitled) (Confluenţe Bibliologice, 2025)
The authors present a rare book collection, owned by the "Nicolae Testemitanu" Medical Scientific Library, belonging to the German bibliophile doctor Richard Koch. In 1937, R. Koch settled in the city of Kislovodsk, and in 1944 he donated part of his library to the Kislovodsk Medical Institute, which in 1945 was transferred to Chisinau. The Koch collection includes approximately 2600 volumes of medicine, biology, philosophy, history. Exclusively, 150 books from the 16th-18th centuries are considered rare books. A special place is occupied by books with Jewish themes. All books in the collection are provided with an ex-libris by R. Koch and enriched with special graphics.